1997
DOI: 10.1152/jn.1997.78.5.2321
|View full text |Cite
|
Sign up to set email alerts
|

Role of Voltage-Gated K+ Currents in Mediating the Regular-Spiking Phenotype of Callosal-Projecting Rat Visual Cortical Neurons

Abstract: Role of voltage-gated K+ currents in mediating the regular-spiking phenotype of callosal-projecting rat visual cortical neurons. J. Neurophysiol. 78: 2321-2335, 1997. Whole cell current- and voltage-clamp recordings were combined to examine action potential waveforms, repetitive firing patterns, and the functional roles of voltage-gated K+ currents (IA, ID, and IK) in identified callosal-projecting (CP) neurons from postnatal (day 7-13) rat primary visual cortex. Brief (1 ms) depolarizing current injections ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 65 publications
7
57
1
Order By: Relevance
“…Because neurons that retract their callosal projections during postnatal development do not die or undergo changes in morphology or transmitter phenotype (Olavarria and Van Sluyters 1985; J. M. Nerbonne and A. Burkhalter, unpublished observations), both the cells that retain and the cells that retract their callosal projections were expected to display regular-spiking behavior. As demonstrated in the subsequent paper (Locke and Nerbonne 1997), current-clamp recordings have revealed that this hypothesis is correct, i.e., all of the cells labeled in early postnatal animals based on the callosal projection are regular-spiking cortical neurons.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Because neurons that retract their callosal projections during postnatal development do not die or undergo changes in morphology or transmitter phenotype (Olavarria and Van Sluyters 1985; J. M. Nerbonne and A. Burkhalter, unpublished observations), both the cells that retain and the cells that retract their callosal projections were expected to display regular-spiking behavior. As demonstrated in the subsequent paper (Locke and Nerbonne 1997), current-clamp recordings have revealed that this hypothesis is correct, i.e., all of the cells labeled in early postnatal animals based on the callosal projection are regular-spiking cortical neurons.…”
Section: Discussionmentioning
confidence: 81%
“…Here, we show that there are three kinetically and pharmacologically distinct Ca 2+ -independent, voltagegated K + currents expressed in CP cells that we refer to as I A , I D , and I K because their properties are similar (although not identical) to I A , I D , and I K currents described in other mammalian central neurons. In the companion paper (Locke and Nerbonne 1997), we demonstrate that CP neurons are indeed regular spiking, and we explore the roles of I A , I D , and I K in shaping the waveforms of action potentials and in regulating the firing properties of CP neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The greatest changes occur between weeks 1 and 3 Lorenzon and Foehring 1993;Locke and Nerbonne 1997a;Maravall et al 2004b;Metherate and Aramakis 1999). Both Kv1 (Guan et al 2006b)-and Kv2 (Foehring et al 2009)-mediated currents regulate interspike intervals in these cells.…”
Section: Development Of Excitability and Firing Patternsmentioning
confidence: 99%
“…Combined action potential and voltage-clamp recordings, for example, suggest that I A channels likely play an important role in action potential repolarization in cortical pyramidal neurons (Kang et al, 2000). It has also been demonstrated that the input resistances of visual cortical neurons are increased in the presence of an often used I A -selective blocker, 4-aminopyridine (4-AP) (Locke and Nerbonne, 1997b). In addition, the current thresholds for action potential generation and the latency to firing are reduced, and action potentials are reportedly prolonged significantly ( p Ͻ 0.001) in the presence of millimolar concentrations of 4-AP (Locke and Nerbonne, 1997b).…”
Section: Action Potentials Are Prolonged In Kv42dn-expressing Corticmentioning
confidence: 99%
“…It has also been demonstrated that the input resistances of visual cortical neurons are increased in the presence of an often used I A -selective blocker, 4-aminopyridine (4-AP) (Locke and Nerbonne, 1997b). In addition, the current thresholds for action potential generation and the latency to firing are reduced, and action potentials are reportedly prolonged significantly ( p Ͻ 0.001) in the presence of millimolar concentrations of 4-AP (Locke and Nerbonne, 1997b). In visual cortical neurons, however, I D is also blocked effectively by millimolar 4-AP (Locke and Nerbonne, 1997a).…”
Section: Action Potentials Are Prolonged In Kv42dn-expressing Corticmentioning
confidence: 99%